The politics of chemistry : science and power in twentieth-century Spain - Nieto-Galan, Agustí (Cambridge : Cambridge University Press, 2019)
Nieto-Galan examines the political role of chemistry in twentieth-century Spain, enriching understandings of the relationship between science and power.
'Technical' ChemistryChemical Diplomacy; 6 Technocratic Progress; 'Neutral' Expertise; Cold War Allies; Corporate Chemistry; 7 Liberal Dissent; Chemists in Exile; Internal Refugees; Conclusion: The Moral Ambiguity of Chemistry; Pure-Applied Chemistry; Modernisation Paradoxes; A Troubled Identity; Chemists as Intellectuals; History and Memory; Addendum: Juan Julio Bonet Sugrañes (1940-2006); Bibliography; Index
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on September 05, 2019).
eBooks on EBSCOhost
Keywords: Chemistry -- Social aspects -- Spain -- History -- 20th century; Chemistry -- Political aspects -- Spain -- History -- 20th century; Science -- Social aspects -- Spain -- History -- 20th century; Science -- Political aspects -- Spain -- History -- 20th century; Science and state; Chimie -- Aspect social -- Espagne -- Histoire -- 20e siècle.; Chimie -- Aspect politique -- Espagne -- Histoire -- 20e siècle.; Sciences -- Aspect social -- Espagne -- Histoire -- 20e siècle.; Sciences -- Aspect politique -- Espagne -- Histoire -- 20e siècle.; Politique scientifique et technique; Chemistry -- Social aspects; Science and state; Science -- Political aspects; Science -- Social aspects; Spain; 1900-1999; History